Beyond Religious Coping: Reconstructing Al-Ghazali's Concept of Tawakal into a Psychospiritual Healing Model for Chronic Anxiety : Melampaui Koping Religius: Merekonstruksi Konsep Tawakal Al-Ghazali menjadi Model Penyembuhan Psikospiritual untuk Kecemasan Kronis - Tistigar Sansayto; Jarman Arroisi; Era Fazira Siregar; Masriyah Sunada Wadi (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
Chronic anxiety has become an increasingly significant mental health challenge, while existing studies have predominantly conceptualized tawakkul as a religious coping strategy without systematically explaining its underlying psychospiritual mechanism. This study aims to reconstruct Al-Ghazali's concept of tawakal into a comprehensive psychospiritual healing framework for addressing chronic anxiety and to examine its theoretical implications for contemporary Islamic psychotherapy. This study employed a qualitative library research design using conceptual analysis. The primary data source was Al-Ghazali's Iḥyāʾ ʿUlūm al-Dīn, particularly Kitāb al-Tawḥīd wa al-Tawakkul, supported by contemporary literature on Islamic psychology, Islamic psychotherapy, and mental health. Data were collected through systematic document analysis and analyzed using thematic content analysis combined with conceptual synthesis. The findings reveal that tawakal is a structured psychospiritual process consisting of five interconnected stages: Tawhid Reinforcement, Cognitive Reorientation, Responsible Human Effort (Ikhtiyār), Tafwīḍ, and Ṭumaʾnīnah. These stages were synthesized into the Al-Ghazali's Tawakal-Based Spiritual Healing (ATSH) Model, which explains how theological beliefs facilitate cognitive transformation, emotional regulation, behavioural engagement, and spiritual restoration in reducing chronic anxiety. The proposed model provides a conceptual foundation for the development of culturally and spiritually responsive Islamic psychotherapy and may inform future counselling, spiritual care, and Muslim mental health interventions. The originality of this study lies in reconstructing Al-Ghazali's classical thought into a systematic psychospiritual healing model, thereby bridging classical Islamic scholarship with contemporary Islamic psychotherapy and providing a theoretical framework for future empirical research.